Prototipo de sistema automatizado para el cultivo de naranja en ambiente controlado (2025)
In the following project, the objective is to develop an automated system that manages the temperature and humidity conditions in a greenhouse for orange cultivation, using a closed-loop PID (Proportional-Integral-Derivative) control for temperature and an ON-OFF control for humidity. The project arises from the need to mitigate the effects of climate change on crops, which significantly affect traditional open-field agriculture. The automation relies on sensors and actuators that monitor and adjust the conditions in the greenhouse, ensuring that they remain within the optimal ranges for orange cultivation: temperatures between 18°C and 30°C and relative humidity between 50% and 60%.